Optimization of biosorption process using cucumis melo rind for the removal of Fe, Mn and Pb ions from groundwater - Mohd Asharuddin, Syazwani (2015)
Biosorption can be an effective technique for the treatment of metal-bearing groundwater. Several fruits and agricultural by-products demonstrated the ability to remove the heavy metals and thereby reduce the water contaminants. In the present study, the potential use of biosorbent material obtained from Cucumis melo rind for the removal of Pb, Fe and Mn ions from groundwater was investigated according to four types of parameters namely pH, biosorbent dosage, initial metal concentration and contact time. Characterization of biosorbent was done by the means of SEM-EDX, XRF and FTIR analysis to observe for the surface morphology, elemental composition and functional groups available on the biosorbent. Sorption was most efficient at pH 7 for Fe(II) and pH 6.5 for both Mn(II) and Pb(II) using 0.05g/100ml biosorbent dosage at contact time of 45 minutes. The biosorption of all metals increased with increasing biosorbent dosage. FTIR study revealed the presence of functional groups on the surface of biosorbent facilitates the biosorption of the metal ions. The Langmuir, Freundlich and BET isotherm models were used to predict the behavior metal binding while Langergren Pseudo-first and Pseudo-second order were used to study the kinetics aspects. The equilibrium data for all metals were best fit to the Langmuir adsorption isotherm with maximum adsorption capacity of 5.3505 mg/g, 2.7525 mg/g and 0.0830 mg/g respectively for Fe(II), Mn(II) and Pb(II). The result indicates that the Pseudo-second order model best describes the kinetics data. The Cucumis melo rind successfully removes up to 90.73%, 91.47% and 90.94% respectively to Fe, Mn and Pb in the groundwater samples which reduce the metals level below the WHO recommended limits of heavy metal for drinking water.